Immunostimulatory properties of dendritic cells after Leishmania donovani infection using an in vitro model of liver microenvironment. - Ludovic Donaghy; Florian Cabillic; Anne Corlu; Octavie Rostan; Olivier Toutirais; Christiane Guguen-Guillouzo; Claude Guiguen; Jean-Pierre Gangneux (Public Library of Science (PLoS), 2010)
BACKGROUND: Recent advances demonstrated that liver dendritic cells (DCs) promote immunologic hyporesponsiveness that may contribute to hepatic tolerance. Although there has been significant work on the phenotypic and functional roles of such DCs, the impact of liver microenvironment on the immune properties of infected DC is still poorly explored, probably because of the limitations of modelization. METHODOLOGY/PRINCIPAL FINDINGS: Here, we hypothesized that DC tolerogenic properties have an impact on the antimicrobial response, particularly during the infection by the protozoan parasite Leishmania donovani. Indeed, a lymphocytic Th2 environment was reported to favour the growth and proliferation of L. donovani. We first modelized an adequate monocyte-differentiated DC model, either in rat liver epithelial cell- or in a human hepatic non-parenchymal cell-conditioned medium in order to infect them further. We established that DCs differentiated in a hepatic microenvironment displayed a CD14+/CD16+/CD123+ phenotype, secreted low IL-12p70 and had an impaired capacity to stimulate allogeneic T lymphocyte proliferation and IFNgamma secretion. We then infected DCs with L. donovani in the in vitro-defined hepatic microenvironment. The infection of hepatic DCs restored their capacity to stimulate allogeneic T-cell proliferation and to induce lymphocytic secretion of IFNgamma. Such characteristics were recently shown to favour granuloma formation in mice liver. CONCLUSIONS/SIGNIFICANCE: Our results suggest that the specific immunostimulatory properties of infected hepatic DCs might amplify the granuloma maturation, which warrants the effective control of infection in the liver during visceral leishmaniasis.